OPTIMASI BIAYA TRANSPORTASI DISTRIBUSI BARANG DENGAN MENGGUNAKAN METODE Northwest Corner (NWC) - Ramadhany Aisyah Rakhim (INFORMAL: Informatics Journal, 2018)
The distribution of goods is closely related to the cost of transportation. The transportation method used by the company will have a major impact on the company's profit. If the profit obtained by the company can be maximized, the company will be able to expand its business to become even bigger. The problem solving step is the determination of optimization criteria and optimization model development. These steps are used to optimize the cost of shipping goods to get maximum profit. The research obtained results namely the cost of shipping goods using the company's NWC method was optimal. It can be concluded that the method of shipping goods that has been carried out by the company has been optimal so that it can continue to be used for further business development, as well as providing an overview that should be done by the company.